2018
DOI: 10.3390/polym10030288
|View full text |Cite
|
Sign up to set email alerts
|

Tube Expansion Deformation Enables In Situ Synchrotron X-ray Scattering Measurements during Extensional Flow-Induced Crystallization of Poly l-Lactide Near the Glass Transition

Abstract: Coronary Heart Disease (CHD) is one of the leading causes of death worldwide, claiming over seven million lives each year. Permanent metal stents, the current standard of care for CHD, inhibit arterial vasomotion and induce serious complications such as late stent thrombosis. Bioresorbable vascular scaffolds (BVSs) made from poly L-lactide (PLLA) overcome these complications by supporting the occluded artery for 3-6 months and then being completely resorbed in 2-3 years, leaving behind a healthy artery. The BV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…One of the issues we have not addressed in this paper is the sequential deformation behaviour whereby the polymer is stretched initially in one direction and subsequently in a second direction. The literature shows that this has a significant effect on the microstructure evolution [31,44] and hence on the constitutive a b behaviour of the materials after stretch [11]. We have generated the relevant data and explored the ability of the model to fit it in a previous study [45] and have demonstrated its capability of capturing this behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…One of the issues we have not addressed in this paper is the sequential deformation behaviour whereby the polymer is stretched initially in one direction and subsequently in a second direction. The literature shows that this has a significant effect on the microstructure evolution [31,44] and hence on the constitutive a b behaviour of the materials after stretch [11]. We have generated the relevant data and explored the ability of the model to fit it in a previous study [45] and have demonstrated its capability of capturing this behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…PLLA’s slow crystallisation kinetics are enhanced through mechanical deformation, resulting in strain-induced molecular orientation [38,39,40,41]. During expansion, the degree of strain (expansion ratio), temperature, deformation mode (simultaneous or sequential) and strain rate are all key to controlling the degree of crystallisation and molecular orientation imparted in the material [29,42,43,44]. It has been reported that to achieve strain-induced crystallisation in PLLA, the degree of strain must be >100% when expanded at a temperature just above T g [45].…”
Section: Introductionmentioning
confidence: 99%
“…The tube parison was heated in a mould to temperatures just above the glass transition temperature (T g ) but below the thermal crystallisation temperature (T cc ) and biaxially deformed by applying internal pressure and axial stretch [23]. The biaxial deformation altered the material morphology and microstructure [24] and hence enhanced the mechanical properties (stiffness, strength and ductility) [18,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Of these conditions, processing temperature (T p ) for stretch blow moulding of PLLA scaffolds has typically been performed at 10~20°C or 20~40°C above T g (~60°C) [18]. The tube parison can be heated inside a hot mould by convection [26] or radiation [24] at a controlled heating time. Processing temperature has previously been observed to influence the tensile modulus and strength when compared at the same hoop strain level [27] and the strain level mainly determined the final orientation [26].…”
Section: Introductionmentioning
confidence: 99%